Sosialisasi Pentingnya Muamalah Berbasis Syariah - Mintarsih, Mimin; Nur’aeni, Nur’aeni (Ma'soem University, 2024)
Islam is a perfect religion because its teachings cover various aspects of human life. Islam teaches us how humans relate to humans (hablum-minannâs). Muamalah is an inseparable part of human life. The problems of muamalah in everyday life in society are deviations and violations that damage economic life and the lives of fellow humans. Therefore, it is necessary to socialize the importance of sharia-based muamalah so that people can understand the benefits and scope of muamalah in everyday life. The method used to solve muamalah problems in society is through 3 stages (planning, implementation, results and evaluation). The results of this socialization include participants starting to understand how to practice muamalah in everyday life, being able to improve and increase the quality of honest values in muaamalah, which will be followed up by directly practicing what has been conveyed in this socialization activity in community life.